Antifungal activity and theoretical study of synthesized pyrazole-imidazole hybrids. Issue 1 (February 2020) - Zinad, Dhafer S.; Mahal, Ahmed; Shareef, Omar A.
Abstract: The density functional theory (DFT) and thermodynamic analyses were applied to study the stability and chemical reactivity of the synthesized CMPIP 2-chloro-4-(4-(1-methyl-1H-pyrazole-4-yl)-1H-imidazole-5-yl) pyridine and MPIMPPA 4-(4-(1-methyl-1H-pyrazole-4-yl)- 1H-imidazole-5-yl)-N-(4-morpholino phenyl) pyridin-2-amine. The results concluded that the CMPIP compound is more stable than MPIMPPA. The antifungal study was confirmed that the MPIMPPA has a higher inhibition zone against Aspergillus niger (A. niger), as compared to the standard drug used, while the CMPIP compound showed weaker activity than the positive control.